An Obsession with Perfection: William Sterndale Bennett and Composers' Block1. Issue 2 (9th December 2016) - Horton, Peter
Abstract : The career of the composer, pianist, teacher and conductor William Sterndale Bennett (1816–1875) provides an excellent example of how early musical promise by no means guarantees adult success. In Bennett's case, enthusiastic, but not undeserved, endorsements from Mendelssohn and Schumann, combined with equally high expectations from his compatriots, proved to be more of a curse than a blessing and resulted in a crisis of confidence. Drawing on many contemporary sources, among them letters, reviews and personal reminiscences, this article investigates the way in which this began to afflict Bennett in his mid-twenties. It manifested itself in various ways: first, he found it increasingly difficult to finish compositions for publication; second, and as a result of this, his output shrank considerably between the early 1840s and the late 1850s; third, most of the works he did complete were on a smaller scale than the earlier ones; fourth, as he is known to have been working on a number of works at this time of which no trace survives, one can only presume that he destroyed them. The burden of expectation, negative criticism and a dread of producing substandard work all contributed to his loss of self-belief, which was also reflected in the observable decline in his ability as a conductor. Lastly, an attempt is made to unravel the curious inverse connection between Bennett's creativity and his marriage, and possible connections between his fantasy overture Paradise and the Peri and Schumann's cantata of the same name. In conclusion, it reflects on the emotional ties between Bennett and two of those particularly close to him, his wife and Schumann, and posits a tentative link between their deaths and his regaining of his compositional voice.